Estimating the Causal Effect of Low Levels of Fine Particulate Matter on Hospitalization. Issue 5 (September 2017) - Makar, Maggie; Antonelli, Joseph; Di, Qian; Cutler, David; Schwartz, Joel; Dominici, Francesca
Abstract : Background: In 2012, the EPA enacted more stringent National Ambient Air Quality Standards (NAAQS) for fine particulate matter (PM2.5 ). Few studies have characterized the health effects of air pollution levels lower than the most recent NAAQS for long-term exposure to PM2.5 (now 12 μg/m 3 ). Methods: We constructed a cohort of 32, 119 Medicare beneficiaries residing in 5138 US ZIP codes who were interviewed as part of the Medicare Current Beneficiary Survey (MCBS) between 2002 and 2010 and had 1 year of follow-up. We considered four outcomes: all-cause hospitalizations, hospitalizations for circulatory diseases and respiratory diseases, and death. Results: We found that increasing exposure to PM2.5 from levels lower than 12 μg/m 3 to levels higher than 12 μg/m 3 is associated with increases in all-cause admission rates of 7% (95% CI = 3%, 10%) and in circulatory admission hazard rates of 6% (95% CI = 2%, 9%). When we restricted analysis to enrollees with exposure always lower than 12 μg/m 3, we found that increasing exposure from levels lower than 8 μg/m 3 to levels higher than 8 μg/m 3 increased all-cause admission hazard rates by 15% (95% CI = 8%, 23%), circulatory by 18% (95% CI = 10%, 27%), and respiratory by 21% (95% CI = 9%, 34%). Conclusions: In a nationally representative sample of Medicare enrollees, changes in exposure to PM2.5, even at levels consistently below standards, are associated with increases in hospital admissions for all causes and cardiovascular and respiratory diseases. The robustness of our results to inclusion of many additional individual level potential confounders adds validity to studies of air pollution that rely entirely on administrative data. Abstract : Supplemental Digital Content is available in the text.